If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7p + 4 = 7 + -2p Reorder the terms: 4 + 7p = 7 + -2p Solving 4 + 7p = 7 + -2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '2p' to each side of the equation. 4 + 7p + 2p = 7 + -2p + 2p Combine like terms: 7p + 2p = 9p 4 + 9p = 7 + -2p + 2p Combine like terms: -2p + 2p = 0 4 + 9p = 7 + 0 4 + 9p = 7 Add '-4' to each side of the equation. 4 + -4 + 9p = 7 + -4 Combine like terms: 4 + -4 = 0 0 + 9p = 7 + -4 9p = 7 + -4 Combine like terms: 7 + -4 = 3 9p = 3 Divide each side by '9'. p = 0.3333333333 Simplifying p = 0.3333333333
| 7x+3(6x+3)=184 | | f(x)=x^2+6x-10 | | 2(675+80n)=2310 | | p/9-5=7 | | x/4-2=5/6+x-4/3 | | (10w-1)(10w+1)=20w | | 6y+2=3y-3 | | 14c-d-7= | | 2/x=-4 | | 3k+15=66 | | ((3x-1)/2)-((5x+4)/3)-((x+2)/8)=((2x-3)/5)-1/10 | | 36-y=-36 | | 7a+3n+3a= | | 4d+12=42 | | x+2+7=40 | | 42-(3c+4)=2(c+4)+c | | 2x+3(2x+15)=125 | | 10(-11-4p)-2p=2(-1-3p) | | 8x-5=1+6x | | 2+675n+80=2310 | | 2+675+80n=2310 | | -8y+5(y+2)=-11 | | 2x+6-7=5-4x | | 4x(x-3)=15 | | 67+5/2x=92 | | 4x+4.2x=5 | | X+3+7=40 | | -46=-6t-8 | | -2+9=16x-5-15x | | 2n+675+80=2310 | | 4x+4.2=5 | | p+8-2=10 |